THE TREATMENT OF BULIMIA-NERVOSA IN PATIENTS WITH DIABETES-MELLITUS - Peveler, R; Fairburn, C (1992)
This paper describes the treatment of a series of patients with bulimia nervosa who also had insulin-dependent diabetes mellitus. The aim was to discover what modifications to an established cognitive behavioral treatment for bulimia nervosa proved necessary to accommodate the presence of diabetes. Treatment of the patients proved more difficult than that of comparable nondiabetic patients. Possible reasons for the difficulties encountered are discussed, together with strategies for overcoming them. It is concluded that cognitive behavior therapy can be successfully modified for the treatment of such patients, although adjunctive psychological and physical treatment techniques are required in some instances. Treatment usually results in improvement in both eating habits and glycemic control, and is likely to reduce the risk of future diabetic complications.